Stress-dependent scaling behavior of dynamic hysteresis in bulk soft ferroelectric ceramic - Rattikorn Yimnirun (2018)
The effects of frequency f, field amplitude E0, and mechanical stress on the hysteresis area 〈A〉 and their scaling relations were investigated on soft PZT bulk ceramics. The hysteresis area was found to depend on the frequency and field amplitude with a same set of exponents to the power-law scaling for both with and without stresses, indicating the universality. The inclusion of stresses into the power law was also obtained in the form of 〈A- A=0 〉 f-0.25 E0 0.44, which indicates the difference of the energy dissipation between the under stress and stress-free conditions and reveals how the hysteresis area decays with increasing stresses. © 2006 American Institute of Physics.